Pengaruh Motivasi, Disiplin, Dan Komitmen Pembimbing Kemasyarakatan Terhadap Kompetensi Klien Pemasyarakatan Di Bapas Kelas 1 Tangerang - Hani Hasanah; Widodo Agung Nugroho (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine whether the partial influence of Motivation (X1) has on Client Competence (Y), the partial influence of Discipline (X2) on client Competence (Y), the partial influence of commitment on client Competence (Y), and the influence of Motivation ( X1), Discipline (X2), Commitment (X3) simultaneously towards Client Competency (Y) at the Tangerang Class 1 Correctional Center. The population of this research is the clients of the Tangerang Class 1 Correctional Center. The sample taken was 50 respondents using the Non-Probability Sampling technique with an Incidental approach, namely a sampling technique based on chance, that is, anyone who happens to meet the researcher can be used as a sample if they are seen to be suitable, with the help of the Statistical Product and Service Solution (SPSS) version version 20. The results of this study show that there is no influence between Motivation (X1) partially on client Competence (Y). This can be shown by t count (0.945) < from t table (2.011), there is no influence between Discipline (X2) as a whole. partial to client competency (Y) this can be shown by t count (-3.329) < from t table (2.011), there is no influence between Commitment (X3) partially to client competency (Y) this can be shown by t count ( 1.606) < from t table (2.011), and the variables of motivation (X1), discipline (X2), and commitment (X3) of community counselors simultaneously on the competency of correctional clients (Y). This can be shown by the results Fcount > ftable (4,683>2,810),